2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346340
|View full text |Cite
|
Sign up to set email alerts
|

Full body gait analysis with Kinect

Abstract: Human gait is an important indicator of health, with applications ranging from diagnosis, monitoring, and rehabilitation. In practice, the use of gait analysis has been limited. Existing gait analysis systems are either expensive, intrusive, or require well-controlled environments such as a clinic or a laboratory. We present an accurate gait analysis system that is economical and non-intrusive. Our system is based on the Kinect sensor and thus can extract comprehensive gait information from all parts of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
145
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(147 citation statements)
references
References 19 publications
0
145
0
2
Order By: Relevance
“…There are many gait recognition approaches published in the literature which are based on point clouds (Tang et al, 2014;Gabel et al, 2012;Whytock et al, 2014;Hofmann et al, 2012), yet they use the widely adopted Kinect sensor which has limited range and a small field-of-view and is less efficient for applications in real life outdoor scenarios than LiDAR sensors. Also the Kinect provides magnitudes higher density than an RMB LiDAR, so the effectiveness of these approaches are questionable in our case.…”
Section: Related Workmentioning
confidence: 99%
“…There are many gait recognition approaches published in the literature which are based on point clouds (Tang et al, 2014;Gabel et al, 2012;Whytock et al, 2014;Hofmann et al, 2012), yet they use the widely adopted Kinect sensor which has limited range and a small field-of-view and is less efficient for applications in real life outdoor scenarios than LiDAR sensors. Also the Kinect provides magnitudes higher density than an RMB LiDAR, so the effectiveness of these approaches are questionable in our case.…”
Section: Related Workmentioning
confidence: 99%
“…Gait is more related to the movement patterns of body parts during locomotion. Gabel et al [22] used the changes in the location of these skeletons between consecutive frames as a feature. However, the work is only evaluated for gait parameter extraction not for identification.…”
Section: Related Workmentioning
confidence: 99%
“…In [16,17] it is shown that gait features extracted from Kinect can be used as a biometric signature. Gabel et al [18] have performed full body gait analysis for continuous gait monitoring at home. Obdrzalek et al [19] have investigated the accuracy of Kinect pose estimation for evaluating physical exercises aimed at coaching of elderly population.…”
Section: Related Workmentioning
confidence: 99%